Colors for Rayon Yarn - E.I. du Pont de Nemours & Company (E.I. du Pont de Nemours & Company, 1926)
According to the work's introduction, "this book has been prepared to acquaint the trade with the large variety of du Pont dyes available for use on rayon and to serve as a guide in the selection of those best suited for individual requirements." The volume includes dyeing instructions, information on the tabulation of dyeing and fastness properties, and finally, twelve pages of rayon samples dyed using DuPont brand dyes.
Keywords: Dyes and dyeing; Dyes and dyeing--Textile fibers; Dyes and dyeing--Rayon; Rayon; Pigments; E.I. du Pont de Nemours & Company